Highway to Hell: The Effect of Product Convenience and Usefulness on Interest in Using Mandiri e-Toll in Makassar City Highway - M. Ikhwan Maulana Haeruddin; Abdi Akbar; Kristina W. Parinsi; Rezky Amalia Hamka; Annisa Paramaswary Aslam (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of the convenience and usefulness of the product on the interest in using Mandiri e-Toll in the people of Makassar City. The population in this study are Mandiri e-Toll e-Money card users. The number of samples used as many as 100 people using a questionnaire. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) v.23. Multiple linear regression equation produces the equation Y = 0.301 + 0.792X1 - 0.192X2. The results of this study found that the convenience and usefulness variables simultaneously had a significant influence on the consumer interest variable. Partially the two independent variables also have a significant influence on the dependent variable. The results of the correlation analysis of determination (R Square) found a value of 0.604 or 60.4%. This means that the percentage of the influence of the independent variables, namely convenience and usefulness, is 60.4%. While the remaining 39.6% is influenced or explained by other variables that are not included in this research model.